1999
DOI: 10.1002/hep.510290230
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Histological Outcome After Hepatitis B E Antigen to Antibody Seroconversion in Children With Chronic Hepatitis B

Abstract: Data regarding the outcome of children with chronic hepatitis B after seroconversion are scarce. We describe the long-term evolution of these patients. One hundred and three children with antibody against hepatitis B e antigen and normal alanine aminotransferase (ALT) levels were followed for 0.6 to 12.5 years (mean, 6.3 years). Paired liver biopsies (before and after seroconversion) were available in 83 cases. Final biopsies were obtained 0.5 to 12.5 years (mean, 4.5 years) after seroconversion. ALT levels re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 28 publications
4
36
0
Order By: Relevance
“…In this study, it was further found that patients with later HBeAg seroclearance had higher frequencies of HBeAg seroreversion and acute exacerbation of chronic hepatitis B after HBeAg seroclearance. Consistent with this finding, the frequency of acute exacerbation after HBeAg seroclearance was reported to be low in previous studies of anti-HBe-positive children (5 to 20%) (5,16). Whether the frequent exacerbation after HBeAg seroclearance in the older age groups leads to the development of cirrhosis-related complications cannot be determined in the present study because of the relatively few complications that developed during the follow-up period.…”
Section: Discussionsupporting
confidence: 85%
“…In this study, it was further found that patients with later HBeAg seroclearance had higher frequencies of HBeAg seroreversion and acute exacerbation of chronic hepatitis B after HBeAg seroclearance. Consistent with this finding, the frequency of acute exacerbation after HBeAg seroclearance was reported to be low in previous studies of anti-HBe-positive children (5 to 20%) (5,16). Whether the frequent exacerbation after HBeAg seroclearance in the older age groups leads to the development of cirrhosis-related complications cannot be determined in the present study because of the relatively few complications that developed during the follow-up period.…”
Section: Discussionsupporting
confidence: 85%
“…If, after termination of interferon treatment, serum HBV DNA concentration was found to be less than 10 4 copies/ml, hepatitis did not occur thereafter (12). However, even after loss of HBsAg and anti-HBs seroconversion, which are considered absolute markers of viral clearance, residual viremia was detected by PCR for several patients for a maximum of 12 months following treatment termination (5,9,18). Similar observations were made for patients with spontaneous loss of HBsAg (9,10,19).…”
mentioning
confidence: 53%
“…33,36,37 In sub-Saharan Africa, Alaska, and Mediterranean countries, transmission of HBV usually occurs from person to person in childhood, whereas perinatal transmission is less common (pattern 2). 25,[38][39][40] In these populations most children who are HBeAg positive have elevated ALT levels and seroconversion to anti-HBe is common near or shortly after the onset of puberty. The third pattern is usually observed in individuals who acquired HBV infection during adulthood.…”
Section: Terminology and Natural History Of Chronic Hbv Infectionmentioning
confidence: 99%
“…This has been referred to as the "inactive carrier state." 29,32,33,39,40,43,45 The course and outcome of the inactive HBsAg carrier state is generally but not invariably benign depending on the duration and severity of the preceding chronic hepatitis. Because fluctuations in ALT and HBV DNA levels are common during the course of chronic HBV infection, serial tests should be performed before patients are determined to be in an inactive carrier state and periodically thereafter.…”
Section: Terminology and Natural History Of Chronic Hbv Infectionmentioning
confidence: 99%